Maximum occlusal force relationship with head and facial pattern in dental students of Shahed university - Mahdi kashani aragh bidi; mahdi jabari jahromi; sepide bagheri hosein abadi; mohammadreza shokuhifar (Tehran University of Medical Sciences, 2020)
Background and Aims: The vertical growth pattern of the face depends on several factors. One of these factors can be the muscle strength of the jaw. Maximum occlusal force (MOF) can be considered as an index to measure the function of the muscles of the masticatory system. Despite the various studies, the relationship between the facial pattern and muscle function is still controversial. According to soft tissue paradigm theory, muscle can affect the shape and form of bones of the jaw, face and head. The aim of this study was to determine the relationship between the maximum occlusal force and head and face growth pattern in dental students of Shahed University in Tehran. Materials and Methods81 dental students (40 males and 41 females) were participated. MOF was measured with a loadcell designed for this purpose, and the anthropometric points of the face and head were measured with digital caliper. Two-way ANOVA and Tukey HSD tests were used to determine the effect of facial and head patterns on the maximum occlusal force. Statistical analysis was performed by SPSS23. Results: The mean MOF in males was 480 N and in females 320 N. Head forms in our sample research were 54.32% Brachycephale, 32.09% Mesocephale, and 13.58% Dolicocephale. The form of the face was 23.45% euprosopic, 39.5% mesoprosopic, and 37.03% leptoprosopic. According to the statistical analysis, the relationship between the maximum occlusal force and leptoprosopic form of face was statistically significant (P=0.02). However, there was not significant relationship between the maximal occlusal force and none of the three type of head forms (P=0.813). Conclusion: MOF was related to the leptoprosopic pattern of face, and these individuals had less bite power. No relationship between the maximum occlusal force and head forms and neither between the head pattern and facial pattern was found in this study. The maximum occlusal force in men was higher in all three facial patterns than that of women, although this relationship was not significant.